Village Government Strategies in Branding Tourism Villages Through Digital-Based Social Mapping in South Tete Batu - Muhammad Ilham; Ikmal Maulana (CV. Abhinaya Indo Group, 2025)
This study is motivated by the tourism industry’s significant potential to boost national income and economic growth in the era of globalization, particularly through the development of tourism villages. The East Lombok Regency government has implemented the policy